Influence of peat and amount and frequency of rain on the mobility of alachlor and terbuthylazine - Sahid, Ismail; Kailasam, Kalithasan; A., Rahman (Universiti Putra Malaysia Press, 1996)
The influence of different levels of peat and amount and frequency of simulated rain on the mobility of alachlor and terbuthylazine in soil was investigated under greenhouse conditions. Movement of the two herbicides down the soil profile) assessed by bioassay using Cucumis sativus) was inversely related to the organic matter content of the soil) but the amount and frequency of rain directly influenced the extent of leaching of the herbicides. In general) terbuthylazine was less mobile than alachlor in the two soils studied) namely Serdang and Selangor series. The phytotoxic levels of terbuthylazine were restricted to the 0 - 15 cm zone in both soils when 640 ml simulated rain was applied over 16 days. Alachlor) on the other hand) moved to depths of20 and 30 cm in Selangor and Serdang series) respectively) when soil columns were exposed to the same watering treatment.